Norbergenin prevents LPS-induced inflammatory responses in macrophages through inhibiting NFκB, MAPK and STAT3 activation and blocking metabolic reprogramming - Li, Wan; Cai, Zhengnan; Schindler, Florian; Bahiraii, Sheyda; Brenner, Martin; Heiss, Elke H.; Weckwerth, Wolfram (Frontiers in Immunology, 2023)
Inflammation is thought to be a key cause of many chronic diseases and cancer. However, current therapeutic agents to control inflammation have limited long-term use potential due to various side-effects. This study aimed to examine the preventive effects of norbergenin, a constituent of traditional anti-inflammatory recipes, on LPS-induced proinflammatory signaling in macrophages and elucidate the underlying mechanisms by integrative metabolomics and shotgun label-free quantitative proteomics platforms. Using high-resolution mass spectrometry, we identified and quantified nearly 3000 proteins across all samples in each dataset. To interpret these datasets, we exploited the differentially expressed proteins and conducted statistical analyses. Accordingly, we found that LPS-induced production of NO, IL1β, TNFα, IL6 and iNOS in macrophages was alleviated by norbergenin via suppressed activation of TLR2 mediated NFκB, MAPKs and STAT3 signaling pathways. In addition, norbergenin was capable of overcoming LPS-triggered metabolic reprogramming in macrophages and restrained the facilitated glycolysis, promoted the reduced OXPHOS, and restored the aberrant metabolites within the TCA cycle. This is linked to its modulation of metabolic enzymes to support its anti-inflammatory activity. Thus, our results uncover that norbergenin regulates inflammatory signaling cascades and metabolic reprogramming in LPS stimulated macrophages to exert its anti-inflammatory potential.